THE MATTER OF RECOGNITION: FANON AND HEGELIAN DIALECTICS - Da Silva, Paulo Cesar Andrade [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2024)
From the Programme of Activities of the International Decade for People of African Descent, proclaimed by the UN General Assembly (2015-2024), this paper proposes a reflection on the recognition of the colonial subject in two dimensions: a) by the denial of the Black man enacted on the poetry of Cruz e Souza and Oswaldo de Camargo; b) by the dialogue that Frantz Fanon holds with Hegel. Fanon observes that the Black man is out of the process of History because he is presented inside the closed circuit of the selfconsciousness or in-itself and never at the critical conscience stage of a being-for-itself because he is not granted recognition reciprocity.
Keywords: recognition; colonial subject; Fanon; Hegel; black Brazilian poetry